Endoscopic treatment of Kaposi’s sarcoma in a heart transplant patient - M. T. Bekov; I. V. Pashkov; N. P. Mozheiko; N. N. Koloskova; K. S. Smirnov; Ya. S. Yakunin; M. V. Olkhovskaya; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Kaposi’s sarcoma (KS) is a malignant tumor caused by human herpesvirus 8. Due to etiological and pathogenetic factors, this type of tumor is common among patients with immunodeficiency of various genesis. Solid organ recipients are at a high risk of developing malignant tumors in various locations due to the peculiarities of subsequent drug immunosuppressive therapy. Because KS is so common in this patient cohort, methods for early detection, efficient treatment, and prevention of the neoplastic process must be developed. This paper presents a clinical case of a successful surgical treatment of KS of the aryepiglottic fold using an endoscopic electrosurgical station with an argon complex.